Case Studies of Battery Energy Storage System Applications in the Brazilian Transmission System - Djalma M. Falcão; Sun Tao; Glauco N. Taranto; Thiago J. Masseran A. Parreiras; Murilo E. C. Bento; Dany H. Huanca; Hugo Muzitano; Paulo Esmeraldo; Pedro Lima; Lillian Monteath; Roberto Brandão (Energies)
This paper presents the preliminary results of studies aiming to use a battery energy storage system (BESS) in the Brazilian transmission system. The main objective of the BESS is to solve congestion problems caused mainly by the large increase in variable renewable generation in certain system areas. The studies were conducted based on actual forecasted system scenarios using a full representation of the electric grid available from the Brazilian system operator data base. In this work, only the steady-state modeling was considered as this may be the first stage in the assessment of a new technology. A qualitative economic comparison of the BESS application with other possible solutions to the congestion problems is also included.